Starostnikom prijazne farmacevtske oblike - Zvonar Pobirk, Alenka (Farmacevtski vestnik, 2017)
An increasing elderly population (people older than 65 years) is leading to a change in global demographics. This presents a new challenge to society and the pharmaceutical industry. For achieving optimal therapeutic effect it is thus essential to focus on developing older patient friendly dosage forms with the particular attention given to the specific physical limitations (e.g. swallowing difficulties, the loss of visual acuity, strength and dexterity), cognitive capabilities (e.g. memory impairment, (un)ability of understanding product use and dosing regimen) and overall health conditions of target patient population. In the present article a review of classical and novel delivery systems for oral, oromucosal, (trans)dermal, parenteral and ophthalmic application focusing on older patient friendly dosage forms is given.
Keywords: farmacevtske oblike; fiksne kombinacije učinkovin; mesto aplikacije; orodisperzibilne oblike; pogostost odmerjanja; prirejeno sproščanje; starostniki; transdermalni obliži; večenotne oblike